(untitled) (शोधसुधा Shodh Sudha, 2023)
The author of this paper discusses the challenges of teaching English language and literature at Nepal Sanskrit University in general and in Pindeshwar Vidyapeeth in particular. Based mainly on the experiences and observations of the author, the paper discusses the challenges of both teaching English for general purposes and teaching English for academic purposes. Moreover, it includes the experiences of fellow teachers of English and the opinions of select students of Pindeshwar Vidyapeeth as well, and has used theories on second language acquisition, foreign language learning and teaching English for academic purposes to support the main argument. The paper concludes that while some of the challenges of teaching English are common to all the universities in Nepal, some are specific to Nepal Sanskrit University alone, and suggests measures to overcome the challenges specific to the university.